The War Came to Me: A Story of Endurance and Survival - Weissman, Eva Broessler; Moore, Gregory J. (Hamilton Books, 2009)
The War Came to Me is a testament to the many persons throughout Europe that risked their lives to save Jews from the extermination effort by the Nazis. This book tells the story of the courageous and compassionate Dutch citizens who helped two young Austrian sisters avoid deportation to the death camps where they almost certainly would have perished. The sisters, Eva and Ruth, were sent by their parents to the Netherlands in order to escape the increasing persecution of Jews in their homeland. They would endure years of separation from their parents and each other, before the family was eventually reunited. Through the daring efforts of these Dutch families, Eva and Ruth were able to escape Nazi persecution and survive the war. Their story serves as a reminder that the best of humanity can be discovered even in the darkest of times.